PENGATURAN PERSYARATAN PROGRAM PEMAGANGAN DI LUAR WILAYAH INDONESIA - I Gusti Agung Ika Laksmi Mahadewi; Ni Nengah Agustin Citrawati (Universitas Mahendradatta, 2025)
Job training is organized and directed to equip, enhance, and develop workcompetencies to improve capabilities, productivity, and well-being. Providing jobtraining is a long-term investment made by a company to develop its own value.Through job training, companies can achieve efficiency and effectiveness in employeeperformance. According to Pangabean, job training is conducted for the benefit ofthree parties: employees, the company, and consumers.